2010
DOI: 10.1590/s0004-27302010000900004
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic and lipidic profile in diabetic patients undergoing dialysis

Abstract: Objective: The aim of this study is to assess the clinical care pattern and to compare the lipid and glycemic profile in a group of diabetic patients undergoing both hemodialysis (HD) and peritoneal dialysis (PD) and to correlate these data using biomarkers of cardiovascular risk. Subjects and methods: The first phase consisted in performing a survey on demographic data, questions about the medical team and glycemic control. In the second phase, patients were assessed through laboratorial data on their glycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
2
0
5
Order By: Relevance
“…Maintenance of the venous catheter is followed by chronic irritation and repeated injury of the endothelial layer of the vein that predispose for the formation of microthrombi [ 14 ]. Prothrombotic state in DM is explained by endothelial injury, hyperfibrinogenaemia and platelet hyperreactivity related to increased glucose levels as well as insulin resistance and hyperinsulinemia [ 15 ]. It was shown that even strict glucose control does not normalize activation of the coagulation system in DM patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the venous catheter is followed by chronic irritation and repeated injury of the endothelial layer of the vein that predispose for the formation of microthrombi [ 14 ]. Prothrombotic state in DM is explained by endothelial injury, hyperfibrinogenaemia and platelet hyperreactivity related to increased glucose levels as well as insulin resistance and hyperinsulinemia [ 15 ]. It was shown that even strict glucose control does not normalize activation of the coagulation system in DM patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Fortes et al 21 (2010), 94% dos pacientes em diálise consideraram o nefrologista o médico responsável por zelar pelo seu controle glicêmico. Todavia 57% dos pacientes tinham HbA1c acima do valor considerado adequado à época.…”
Section: Cuidados Primários Mfc Nefrologistaunclassified
“…Todavia 57% dos pacientes tinham HbA1c acima do valor considerado adequado à época. Pacientes em DP apresentavam valores de HbA1c significativamente maiores quando comparados aos de pacientes em HD (9,37 ±0,5) vs (7,37 ±0,49), p <0,01 21 .…”
Section: Cuidados Primários Mfc Nefrologistaunclassified
“…Os dados para a formatação do questionário foram selecionados a partir das informações contidas na literatura. (Deighan C. J, 2000 ;Fortes P. C, 2010).…”
Section: Metodologiaunclassified